TRANSITIVITY ANALYSIS OF KEYNOTE SPEECH OF JOKO WIDODO AT WEF EA 2015 - Mardiono, Mardiono (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
International political speeches have played an extremely important role in political environment and take broader public attention due to their political, economy, and cultural values manifested through the language used. Systemic–Functional Grammar introduced and developed by Halliday (1967) sets out that with languages there are ideational meta-function, interpersonal meta-function, and textual meta-function. Hiring the theory of transitivity from Halliday’s Systemic Functional Linguistics, this study focuses on analysing Joko Widodo’s keynote speech. The aim is to figure out the deeper meaning of the speech through the distributions and so the dominations of the transitivity processes along with their participants. At the same time this study tries to find out the hidden information by analysing the functions of the transitivity processes and the main participants. The qualitative method is employed for the transitivity analysis while the quantitative method is taken to provide the statistic description on the distributions of the types of the process and the participants found. The analysis generates two major findings: First, there are five types of process: material, relational, verbal, mental, existential and the participants found, and no single behavioural process and its participants occurred. Among them, the material process and relational process along with their participants dominate the speech, which makes it well-delivered, more powerful, objective, and convincing. Second, the pronouns ‘we, our, and us’ are found as the main participants in Joko Widodo’s keynote speech that indicate his efforts to draw a close relation between him and his audience so his addressing has succeeded.